Assessment of community knowledge on non-communicable diseases to inform the pilot of WHO PEN-Plus initiatives in selected two districts in Tanzania - Gibson B. Kagaruki; Peter Mathias Karoli; Willfredius M. Rutahoile; Pilly Chillo; Reuben Mutagaywa; Aidan Banduka; Edna Siima Majaliwa; Renatus Fabiano Nyarubamba; Esther Mtumbuka; Elizabeth Mallya; Katunzi Mutalemwa; Noemi Bazzanin; et al. (PLoS ONE, 2025)
Background Non-communicable diseases (NCDs) have increased significantly in Tanzania, accounting for 33% of mortality in the country. Having adequate knowledge translated into practice has a significant effect on the health of individuals through adoption of positive behaviours and influencing better health seeking behaviours. For those already affected by NCDs, it promotes secondary and tertiary prevention by helping them effectively cope with the disease. In this study, we aimed to determine the level and determinants of NCDs knowledge in the community to inform the implementation of WHO PEN- Plus initiatives. Methods This cross-sectional study was conducted from May to June 2023 involving 528 adults aged 25–64 years from two purposely selected districts and 11, 22 and 528 randomly selected wards, villages, and households respectively. Information on socio-economic, demographic, NCDs knowledge were collected from each participant. Chi-square test and Modified Poisson Regression were applied to assess the association and determinants of NCDs knowledge level. Results The median age of study participants was 40.5 years. Less than half 42.6%(n=225) were aware of the term NCD and less than one third were aware of the NCD conditions such as Type 1 Diabetes Mellitus (T1DM) 15.3%(n=70), Sickle Cell Disease (SCD) 25.2%(n=133), Rheumatic fever 28.6%(n=151) and Heart failure 33.1%(n=175). Good level of awareness was reported on Type 2 Diabetes Mellitus (T2DM) 79.5%(n=364). More than three quarters of the respondents had low knowledge on T1DM (90.3%), SCD (84.1%), Rheumatic fever (81.3%), NCDs (80.5%) and Heart failure (76.1%). Furthermore, more than half (56.4%) of respondents had low knowledge for T2DM. Adjusted analysis indicated that, for all NCDs except SCD, low knowledge was significantly associated with the district of residence (Kondoa). Low knowledge of NCDs, T2DM, and SCD was significantly associated with having no education, or having only primary or secondary education. Individuals from the lowest, second, middle, and fourth socio-economic status families were significantly associated with low knowledge of NCDs, while the lowest and fourth socio-economic status levels were associated with low knowledge of T2DM and SCD. Conclusion Low knowledge was observed for all NCDs conditions and socio-economic and demographic characteristics were associated with low knowledge. Interventions to increase NCDs knowledge should consider the socio-economic determinants.